EMPLOYEE JOB SATISFACTION AND ORGANIZATIONAL PERFORMANCE: A STUDY ON MANUFACTURING SECTOR IN BANGALORE - Ms.Hemalatha S; Mrs. JanakiBai S; Sheka K, Mr. Arjun (The journal of contemporary issues in business and government, 2022)
In this study, we take a hard look at how contented workers' attitudes in the workplace affect business outcomes for both big and medium-sized manufacturers. It emphasises that happy workers are more productive and efficient in the workplace. According to the study, a happy worker is one who appreciates his or her position in the company. On the other hand, a negative outlook on the job is indicative of an individual who is unhappy in his position. The motivation behind this examination is to decide if there is an observationally provable connection between job satisfaction and organizational performance and if so, what direction and strength does this relationship take among employees working in the manufacturing sector in Karnataka. Ten firms from both major and medium-sized industries were chosen as the basis for the empirical study, and a total of 155 workers were polled. According to the results, there is a little however critical connection between representative work fulfillment and hierarchical execution. The results of the study showed that employee happiness had a greater impact on business success than had business success on employee happiness.